Clinical Features and Temporal Changes of RT-PCR and Chest CT in COVID-19 Pediatric Patients - Xia, Wei; Guo, Yu; Tian, Zhiyao; Luo, Yan; Hu, Daoyu; Shao, Jianbo; Li, Zhen; Kamel, Ihab R. (Frontiers in Pediatrics, 2020)
Objective: To investigate the clinical features and temporal changes of RT-PCR and CT in COVID-19 pediatric patients. Methods: Clinical, RT-PCR and CT features of 114 COVID-19 pediatric inpatients were retrospectively reviewed from January 21st to March 14th 2020. All patients had chest CT on admission and were identified as positive pharyngeal swab nucleic acid test. Clinical features were analyzed, as well as the features and temporal changes of RT-PCR and CT. Results: Fever (62, 54%) and cough (61, 54%) were the most common symptoms. There were 34 (30%) cases of concurrent infections. The most common imaging features on CT were ground-glass opacities (46, 40%) and consolidation (46, 40%). The bilateral lower lobes were the most common pattern of involvement, with 63 cases (55%) involving 1-2 lobes, and in 32 (28%) cases CT was normal. Through the whole duration of COVID-19 in children, the diagnostic positive rate of RT-PCR has been far higher than that of CT (All P＜·05). For RT-PCR follow-up, reliable negative results were obtained only 7 days after the onset of symptoms. Though Lung involvement on chest CT progressed rapidly in several cases, lung involvement in children with COVID-19 is mild, with a median value of 2 on CT score. Conclusions: RT-PCR is more reliable than CT in initial diagnosis of pediatric patients with COVID-19. On follow up, reliable negative RT-PCR results are available 7 days after initial symptoms. The use of CT should be considered for follow-up purposes only if necessary.